2011
DOI: 10.1111/j.1755-3768.2011.02126.x
|View full text |Cite
|
Sign up to set email alerts
|

Miyake-Apple view of inner side of sclerotomy during microincision vitrectomy surgery

Abstract: . Purpose:  To examine the inner surface of the sclerotomy during microincision vitrectomy surgery by Miyake‐Apple view. Methods:  The anterior half of porcine eyes was attached to a transparent acrylic plate with cyanoacrylate glue. Then, either a 23‐gauge or a 25‐gauge trocar‐cannula was inserted through the sclera obliquely. The inner surface of the entrance site was observed posteriorly by Miyake‐Apple view. These images were compared with the endoscopic view of two patients who underwent vitreous surgery … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 24 publications
0
13
0
Order By: Relevance
“…In fact, we found vitreous strands in practically all the sclerotomies analyzed (93.2% and 95.8%, depending on the incisional subgroup evaluated), as had been previously described by other studies that used an endoscopic video probe 10 or an external video camera system (MiyakeApple exploration). 11 Therefore, regardless of the element inserted through the cannula during its extraction, and in spite of performing intense vitreous shaving around the incision sites during the operation, it was not possible to leave the perisclerotomy region free of vitreous in almost any sclerotomy after the vitrectomy. This high rate of vitreous incarceration may be caused by the inserted cannulas, which protrude 2 to 3 mm into the vitreous cavity, possibly impeding complete clearing of the vitreous that surrounds the cannula.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In fact, we found vitreous strands in practically all the sclerotomies analyzed (93.2% and 95.8%, depending on the incisional subgroup evaluated), as had been previously described by other studies that used an endoscopic video probe 10 or an external video camera system (MiyakeApple exploration). 11 Therefore, regardless of the element inserted through the cannula during its extraction, and in spite of performing intense vitreous shaving around the incision sites during the operation, it was not possible to leave the perisclerotomy region free of vitreous in almost any sclerotomy after the vitrectomy. This high rate of vitreous incarceration may be caused by the inserted cannulas, which protrude 2 to 3 mm into the vitreous cavity, possibly impeding complete clearing of the vitreous that surrounds the cannula.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, our results are similar to those observed in human research. 10,11 The important outcome of our study is the relative difference in vitreous entrapment grade detected in sclerotomies whose cannulas were extracted with the light pipe or the plug inserted.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Reported incidence rates for vitreous incarceration at the sclerotomy site of microincision sutureless vitrectomy are variable 11,13,24,2833. Using ultrasound biomicroscopy, Gutfleisch et al30 reported that the incidence of vitreous incarceration decreased from 40% to 20% at the sclerotomy sites using a 23-gauge two-step system compared with a sclerotomy site using a 23-gauge one-step system; in their study, the cannulas were simply removed.…”
Section: Discussionmentioning
confidence: 99%
“…In a study of sclerotomy sites in rabbits,32 vitreous incarceration occurred in 59.4% of cases. Inoue et al33 found vitreous strands incarcerated at the sclerotomy site in porcine eyes by Miyake-Apple view and in human eyes using endoscopy. These inconsistencies in incidence rates for vitreous incarceration may be due to the different surgical techniques used and the differences between human eyes and experimental models.…”
Section: Discussionmentioning
confidence: 99%